Formulation and Characterization of Self-Microemulsifying Drug Delivery System of Tacrolimus - Duaa J. Al-Tamimi; Ahmed A. Hussein (College of Pharmacy University of Baghdad, 2021)
Abstract The present investigation aimed to formulate a liquid self-microemulsifying drug delivery system (SMEDDS) of tacrolimus to enhance its oral bioavailability by improving its dispersibility and dissolution rate. Four liquid SMEDDS were prepared using maisine CC as oil phase, labrasol ALF as surfactant and transcutol HP as co-surfactant based on the solubility studies of tacrolimus in these components. The phase behavior of the components and the area of microemulsion were evaluated using pseudoternary phase diagrams. The formulations were also assessed for thermodynamic stability, robustness to dilution, self-emulsification time, drug content, globule size and polydispersity index. The prepared SMEDDS formulations exhibited improved drug release compared to the pure drug powder. From this study, it was concluded that using a composition of 10% maisine CC, 67.5% labrasol ALF and 22.5% transcutol produced a liquid SMEDDS with good thermodynamic stability and enhanced in-vitro drug release profiles compared with pure tacrolimus powder. All which supports the use of self-micro emulsifying drug delivery systems as a promising approach to improve solubility, dissolution and stability of poorly soluble drugs like tacrolimus.